IDENTIFICATION OF FORMALIN CONTENT IN SOME FRESH SALTWATER FISH AT X TRADITIONAL MARKET, PAYAKUMBUH - Usma Aulia; Ulfa Rahmi Putri; Anna Zukiaturrahmah; Juliadi Ramadhan; Darwis; Sri Rezeki (Buletin Veteriner Udayana, 2026)
Fish is a food source with high protein content and is relatively more affordable compared to other animal-based protein sources. A common issue is the misuse of hazardous substances to prevent quality deterioration and increase profit, such as formalin. This study aimed to identify the presence of formalin in fresh marine fish sold at Traditional Market X, Payakumbuh, to ensure food quality and safety for public consumption. Formalin testing was conducted on 10 samples, each weighing 10 g. Twenty milliliters of aquadest were added to each sample, followed by homogenization using a stomacher. The samples were then centrifuged at 3000 rpm for two minutes. After centrifugation, 10 mL of the supernatant from each sample was transferred into test tubes. Each tube was added with 3 drops of 0.5% phenylhydrazine, 2 drops of 5% sodium nitroprusside, and 3 drops of 10% NaOH, and the results were observed. The results showed that none of the samples contained formalin, as indicated by the absence of color change; all samples remained reddish-orange after reagent addition. Therefore, fresh marine fish sold at Traditional Market X Payakumbuh, were confirmed to be free from formalin and safe for consumption. Routine monitoring by the government is recommended to prevent the misuse of hazardous substances such as formalin in food products.